Development of a laboratory scale reactor with controlled high pressure sampling for subcritical Methanolysis of biodiesel - Anusan Permsuwan (2018)
The objective of this work was to develop a laboratory scale reactor for biodiesel production from subcritical methanol transesterification. The design was based on utilizing a high pressure system from diesel engine to regulate near critical condition and sample the converted product. The reactor consisted of a 400 ml autoclave, a 2-kW electrical heating furnace, and a product sampling system. The pressure system was adapted from a diesel fuel injector. High pressure and temperature inside the reactor was built up by means of external heat source. Rapid heat transfer was provided to the reactor, accompanied with simultaneous rise in pressure so that near critical conditions (temperatures between 180-200 °C and pressure around 140-190 atm) were attained for methanol. Synthesis product can be collected real time via injection. Limited product samples from preliminary tests with palm oil and methanol at molar ratio of 46:1 were collected and analyzed by gas chromatography - mass spectrometry. Analysis results showed high percentage conversion of vegetable oil to methyl esters. Yields of over 93% biodiesel were obtained. The reactor proved to be successful for producing biodiesel.